Pendampingan Pelayanan Pemadanan NIK NPWP pada Kantor Pelayanan Pajak Pratama (KPP) Sidoarjo Barat - Ifta Takhul Laiya; Sakina Nur Hayati; Whindi Ayu Mayrena; Kafidin Muzakki (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Data matching of Population Identification Number (NIK) as Taxpayer Identification Number (NPWP) needs to be done. This is an order from Law (UU) Number 7 of 2021, Presidential Regulation Number 83 of 2021, and Regulation of the Minister of Finance Number 112/PMK.03/2022. Regarding the implementation of data matching of NIK to NPWP which must be accelerated. The Directorate General of Taxes (DJP) of the Ministry of Finance (Kemenkeu) has set the time for matching NIK to NPWP to be fully implemented in mid-2024. Tax Volunteers support Taxpayers (WP) in matching Population Identity Number (NIK) and Taxpayer Identification Number (NPWP). Matching NIK NPWP functions as part of the steps to improve tax compliance and administration in Indonesia. The purpose of this comparison is to inform the truth and reliability of personal data and tax information of Indonesian citizens.